auto-update(nvim): 2025-01-23 15:28:18
This commit is contained in:
parent
ba14b89a35
commit
099089e55e
1 changed files with 143 additions and 1 deletions
|
@ -338,7 +338,7 @@ Consider the IVP
|
|||
$ y' = 1 / 2 cos(y) + t, y(0) = -1 $
|
||||
|
||||
The righthand side is nice, by @eutheorem, it has a unique solution. We can't
|
||||
find an explicit solution.
|
||||
find an explicit solution. So use Euler's method.
|
||||
|
||||
= Lecture #datetime(day: 23, month: 1, year: 2025).display()
|
||||
|
||||
|
@ -387,4 +387,146 @@ has a unique solution $y(t)$ defined on $I$. Same as first order case. Always wr
|
|||
|
||||
== 2nd order linear homogenous ODEs
|
||||
|
||||
How to find solutions to 2nd order linear ODE? Recall
|
||||
|
||||
$
|
||||
y'' = p(t)y' + q(t)y = 0
|
||||
$
|
||||
|
||||
Consider 2nd order linear homogenous ODEs with constant coefficients $a,b,c, a!= 0$.
|
||||
|
||||
$
|
||||
a y'' + b y' + c y = 0
|
||||
$
|
||||
|
||||
Judging from this equation it seems $y$ should be an exponential since we want
|
||||
a function whose derivatives can cancel each other out (with constants
|
||||
applied).
|
||||
|
||||
Trying $y=e^(r t)$,
|
||||
|
||||
$
|
||||
y' = r e^(r t) \
|
||||
y'' = r^2 e^(r t) \
|
||||
a r^2 e^(r t) + b r e^(r t) + c e^(r t) = 0
|
||||
$
|
||||
|
||||
$e^(r t)$ is never 0 (in $RR$) so we can divide without losing or gaining solutions.
|
||||
|
||||
$
|
||||
e^(r t) (a r^2 + b r + c) = 0
|
||||
$
|
||||
|
||||
Then we simply just need to solve a quadratic for $r$.
|
||||
|
||||
$
|
||||
a r^2 + b r + c = 0
|
||||
$
|
||||
|
||||
We may have two distinct real solutions, one repeated solution, or complex
|
||||
solutions (no solutions in $RR$). For now let us consider the distinct real
|
||||
solutions.
|
||||
|
||||
#fact[
|
||||
We conclude $y(t) = e^(r t)$ is a solution of
|
||||
$
|
||||
a y'' + b y' + c y = 0
|
||||
$
|
||||
provided $r$ satisfies
|
||||
$
|
||||
a r^2 + b r + c = 0
|
||||
$
|
||||
This is the _characteristic equation_.
|
||||
]
|
||||
|
||||
#example[
|
||||
$
|
||||
y'' + 5y' + 6y = 0
|
||||
$
|
||||
It is homogenous, so we find the characteristic equation.
|
||||
|
||||
$
|
||||
r^2 + 5 r + 6 = 0 \
|
||||
r = -2, -3 \
|
||||
y_1 = e^(-2t), y_2 = e^(-3t)
|
||||
$
|
||||
]<particular-solutions>
|
||||
|
||||
#example[
|
||||
$ y'' - 2y' + y = 0 $
|
||||
The characteristic equation is
|
||||
$
|
||||
r^2 - 2r + 1 = 0 \
|
||||
r = 1 \
|
||||
y_1 = e^t
|
||||
$
|
||||
]
|
||||
|
||||
== Superposition principle for 2nd order linear homogenous ODE
|
||||
|
||||
We can find a few particular solutions to our ODE, but how can we find all of the solutions?
|
||||
|
||||
#fact[
|
||||
Suppose $y_1(t), y_2(t)$ are a pair of solutions of
|
||||
$
|
||||
y'' + p(t) y' + q(t) y = 0
|
||||
$
|
||||
Then the linear combination
|
||||
$
|
||||
c_1 y_1(t) + c_2 y_2(t)
|
||||
$
|
||||
is also a solution.
|
||||
]<superposition-principle>
|
||||
|
||||
#proof[
|
||||
$
|
||||
(c_1 y_1(t) + c_2 y_2(t))'' + p(t) (c_1 y_1(t) + c_2 y_2(t))' + q(t)(c_1 y_1(t) + c_2 y_2(t)) \
|
||||
= c_1 y_1'' + c_2 y_2'' + p(t)(c_1 y_1' + c_2 y_2') + g(t)(c_1 y_1 + c_2 y_2) \
|
||||
= c_1 (y''_1 + p(t)y'_1 + q(t) y_1) + c_2 (y''_2 + p(t) y'_2 + q(t) y_2) \
|
||||
= c_1 (0) + c_2(0) = 0
|
||||
$
|
||||
]
|
||||
|
||||
#example[Revisiting @particular-solutions][
|
||||
$
|
||||
y'' + 5y' + 6y = 0
|
||||
$
|
||||
It is homogenous, so we find the characteristic equation.
|
||||
|
||||
$
|
||||
r^2 + 5 r + 6 = 0 \
|
||||
r = -2, -3 \
|
||||
y_1 = e^(-2t), y_2 = e^(-3t)
|
||||
$
|
||||
|
||||
So by @superposition-principle,
|
||||
$
|
||||
y(t) = c_1 e^(-2t) + c_2 e^(-3t)
|
||||
$
|
||||
is a general solution.
|
||||
]
|
||||
|
||||
#example[
|
||||
Find the general solution of
|
||||
$
|
||||
y'' + 2y' - 3y = 0 \
|
||||
y(1) = 1, y'(1) = -1
|
||||
$
|
||||
and then find the solution satisfying the initial conditions
|
||||
$
|
||||
y(1) = 1, y'(1) = -1
|
||||
$
|
||||
General solution is
|
||||
$
|
||||
y(t) &= c_1 e^(-3t) + c_2 e^t \
|
||||
y'(t) &= -3 c_1 e^(-3t) + c_2 e^t
|
||||
$
|
||||
Now we need the particular solution.
|
||||
$
|
||||
1 &= c_1 e^(-3) + c_2 e \
|
||||
-1 &= -3 c_1 e^(-3) + c_2 e \
|
||||
$
|
||||
|
||||
Now we have a system and we can solve it using standard linear algebra
|
||||
techniques.
|
||||
]
|
||||
|
|
Loading…
Reference in a new issue